GENDER DIFFERENCES IN READING COMPREHENSION ACHIEVEMENT (A CASE STUDY AT IAIN SYEKH NURJATI CIREBON) - Jefy Fauzan (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2016)
Abstract Language and gender have become a comprehensive issue in language learning. One aspect that is highlighted in language and gender is reading skill. The term of gender plays different perfomance and achievement in reading comprehension. There are some influences of gender differences toward reading comprehension achievement. This study aims to investigate such gender differences in achieving comprehension of factual text. This thesis is qualitative study case analysis.The primary sources of data are conducted through reading comprehension test and interview in order to investigate gender differences among EFL learners of IAIN Syekh Nurjati Cirebon in reading comprehension achievement. The result shows that gender differences influence in reading comprehension achievement. Different trait from family and society will influence students reading achievement. It is found that 25% of boys’ participants get high score in reading comprehension test and 33% girls participants get high score in reading comprehension test and those differences are caused by different trait of their family and society toward reading. The study also comes to gender differences in achieving factual text. Boys tend to use such discussion in post reading strategy while girls tend to use writing activities in post reading strategy. Girls are strong in the skills of determining meaning of unfamiliar words while boys strong in the skills of find particular informations from the text.